The Role of Natural Drug Silymarinin in Chronic Liver Disease Patients - Shabir Hussain, Muhammed Omer Khan, Amjad Mustafa, Ghazala Shaheen, Sumera Feroz, Shafiq Ahmad (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Prediabetic patients and healthy overweight people also tend to suffer from NAFLD, but researchers have only scratched the surface of this condition. This study analyses the effect of hepatic steatosis on fibrosis and evaluates the key predictors of liver injury in prediabetes to see if the liver damage induced by prediabetes can be restored by adopting a Mediterranean diet and taking the nutraceuticalsilymarin. Place and Duration: In the department of Medicine of KGN Teaching Hospital/Bannu Medical College,Bannu for the duration of one year from 1st June 2019 to 30th May 2020. Methods: A total of 212 prediabetic individuals without a previous diagnosis of NAFLD and 126 healthy controls underwent a clinical evaluation, transient elastography evaluating liver stiffness (LS), and a controlled attenuation parameter (CAP). Subsequently, 212 patients at risk for developing diabetes participated in a prospective randomised interventional study, with 104 assigned to a Mediterranean diet alone and 108 assigned to a Mediterranean diet plus supplementation with silymarin (a flavonolignan complex isolated from Silybum marianum and Morus alba). Six months of treatment with 420 milligrams of silymarin twice daily. Participants underwent follow-up clinical and instrumental evaluations after the 6-month experiment period ended. Genotyping for patatin-like phospholipase domain containing 3 in prediabetic individuals (PNPLA3). Results: To date, natural products and their derivatives have accounted for over 50% of the natural remedies used to treat liver disorders. Despite natural medicine’s many benefits and low risk, clinicians should be aware of the potential for adverse reactions such as liver injury, interstitial pneumonia, and abrupt respiratory failure. This means that when using naturopathic regimens to treat liver disorders, we must do everything in our power to prevent and avoid the negative influence of these drugs as much as possible. Using real-world examples to stress the importance of preventing and managing adverse reactions to the natural agents, this article explores the current application and proposed improvements of natural medicine in the treatment of liver illnesses. Conclusion: Silymarin has demonstrated effectiveness as a supportive treatment for the majority of liver diseases, including cirrhosis and alcohol-induced liver damage. Among patients with cirrhosis, silymarin therapy resulted in a substantial decrease in fatalities due to liver complications in clinical trials. Keywords: Liver illness, Cautions, Adverse Reactions, Herbal Medicine, Natural Nutraceuticals.